Mouse models and human islet transplantation sites for intravital imaging - Wagner, Leslie E.; Melnyk, Olha; Duffett, Bryce E.; Linnemann, Amelia K. (Frontiers in Endocrinology, 2022)
Human islet transplantations into rodent models are an essential tool to aid in the development and testing of islet and cellular-based therapies for diabetes prevention and treatment. Through the ability to evaluate human islets in an in vivo setting, these studies allow for experimental approaches to answer questions surrounding normal and disease pathophysiology that cannot be answered using other in vitro and in vivo techniques alone. Intravital microscopy enables imaging of tissues in living organisms with dynamic temporal resolution and can be employed to measure biological processes in transplanted human islets revealing how experimental variables can influence engraftment, and transplant survival and function. A key consideration in experimental design for transplant imaging is the surgical placement site, which is guided by the presence of vasculature to aid in functional engraftment of the islets and promote their survival. Here, we review transplantation sites and mouse models used to study beta cell biology in vivo using intravital microscopy and we highlight fundamental observations made possible using this methodology.